Chaetomitrium Elongatum - Monica Suleiman; Hiroyuki Akiyama (Museum of Nature and Human Activities, 2014)
(1) Branches are recurved to incurved when dry, densely foliate, flattened to sub-tumid, often secund and blunt but sometimes cuspidate; (2) branch leaves are rugose above, deeply concave, and apices are rugose or recurved, mucronate to short-acute; (3) leaf margins are bluntly denticulate with geminate teeth but almost entire to denticulate across apices; (4) lamina cells are thick-walled, prorate, and sub-rhomboidal near apices; (5) calyptrae (immature) are hispid, with long cilia at the base.